Analysis of Internal Control of Fixed Assets as an Effort to Prevent Fraud: A Case Study at Universitas Pembangunan Panca Budi - Nur Aziza; Rahima Br Purba; Renny Maisyarah (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Inadequate internal control over fixed assets can increase the risk of fraud within an organization. Therefore, this study aims to analyze the effect of fixed asset internal control on fraud prevention at Universitas Pembangunan Panca Budi. Internal control in this study is measured based on the five components of the COSO internal control framework, namely control environment, control activities, risk assessment, information and communication, and monitoring. This study employs a quantitative approach using a survey method by distributing questionnaires to respondents involved in the management and utilization of fixed assets. The collected data were analyzed using multiple linear regression with the Ordinary Least Squares (OLS) approach and processed using the EViews application. Prior to regression analysis, classical assumption tests were conducted, including normality, multicollinearity, and heteroskedasticity tests. The results indicate that, simultaneously, fixed asset internal control has a significant effect on fraud prevention. Partially, the control environment, control activities, information and communication, and monitoring have a positive effect on fraud prevention, while risk assessment does not have a significant effect. The classical assumption test results show that the data are normally distributed, free from multicollinearity, and do not exhibit heteroskedasticity, indicating that the regression model is appropriate for use. Based on these findings, it can be concluded that strengthening fixed asset internal control plays an important role in fraud prevention efforts. Therefore, the institution is encouraged to continuously enhance the effectiveness of its internal control system, particularly in the aspects of risk assessment and continuous monitoring.